2021
DOI: 10.1016/j.cjco.2021.08.011
|View full text |Cite
|
Sign up to set email alerts
|

Sex Differences in the Care Experiences of Patients Hospitalized Due to Ischemic Heart Disease in Alberta, Canada

Abstract: This is a PDF file of an article that has undergone enhancements after acceptance, such as the addition of a cover page and metadata, and formatting for readability, but it is not yet the definitive version of record. This version will undergo additional copyediting, typesetting and review before it is published in its final form, but we are providing this version to give early visibility of the article. Please note that, during the production process, errors may be discovered which could affect the content, a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(9 citation statements)
references
References 31 publications
(44 reference statements)
0
9
0
Order By: Relevance
“…The impact and influence of gender on patient experience and PREMS is increasingly recognised. Females consistently report fewer positive experiences of healthcare and lower scores for both physical and mental health [11][12][13][14][15]. To date, gender differences in PREMS of people with kidney disease have not been explored.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The impact and influence of gender on patient experience and PREMS is increasingly recognised. Females consistently report fewer positive experiences of healthcare and lower scores for both physical and mental health [11][12][13][14][15]. To date, gender differences in PREMS of people with kidney disease have not been explored.…”
Section: Discussionmentioning
confidence: 99%
“…The impact of gender on patient experience is an area of growing interest. Differences in general patient satisfaction between males and females was first noted over fifteen years ago [10], but it is only more recently that this has been explored in more detail [11][12][13][14][15]. Females consistently report fewer positive experiences and have lower scores for both physical and mental health.…”
Section: Gender Differences In Experiences and Expectations Of Haemod...mentioning
confidence: 99%
“…Sex differences in the experiences of patients hospitalized due to ischaemic heart disease [39] Examine the comprehensive experience of patients hospitalized due to ischemic heart disease, according to sex.…”
Section: Cpes-ic Dadmentioning
confidence: 99%
“…Some of these studies have concluded that women tend to be more satisfied with physicians and/or medical care received compared to the men group [31]. Other studies found that gender did not significantly influence satisfaction [27,56]. For instance, Otani et al [56] observed that women tended to evaluate their experience with nurses as having a greater importance in the overall satisfaction, while men evaluated their experience with physicians as more important.…”
Section: Satisfactionmentioning
confidence: 99%
“…Several studies indicated that the beneficial influence of green/natural environment may be different for males and females [20][21][22][23][24][25][26]. Some of these studies revealed that the effect of exposure to green environment was higher for males than for females [24,26], while other studies showed no gender differences [23,27] or a higher effect in the female group [21,28,29]. In the healthcare context, Tucker and Kelley [30] have investigated the difference in satisfaction between males and females and reported a positive and significant association between male patients and higher levels of satisfaction.…”
Section: Introductionmentioning
confidence: 99%